Fuel cell system, and control method for fuel cell system - Naganuma, Yoshiaki; Mizuno, Nobukazu (2019)
A fuel cell system includes: a fuel cell supplied with fuel gas for power generation; a fuel supply flow passage flowing fuel gas, supplied from a fuel supply source, to the fuel cell; a pressure regulating valve regulating a pressure of fuel gas flowing through the fuel supply flow passage; a fuel circulation flow passage returning gas, emitted from the fuel cell, to the fuel supply flow passage; a circulation pump delivering gas in the fuel circulation flow passage to the fuel supply flow passage; an emission valve emitting gas in the fuel circulation flow passage to an outside; and a control device controlling the pressure regulating valve, the circulation pump and the emission valve such that the sum of losses of crossover hydrogen, circulation pump power and purge hydrogen is minimum while a hydrogen stoichiometric ratio required for power generation of the fuel cell is ensured.